Dangdut Rakyat Melawan Hegemoni Keraton: Dekonstruksi Pertarungan Ideologis dalam Film Ambyar Mak Byar - Ilham Baskoro; Dimas Septo Nugroho; Diah Ariani Arimbi; Johny Alfian Khusyairi (HUMANIKA, 2026)
This study critically examines Ambyar Mak Byar as ideological contestation between people’s dangdut culture and the hegemonic authority of the Javanese Keraton through Jacques Derrida’s deconstructive framework. Focusing on logosentrism, binary oppositions, différance, and narrative deconstruction, this research analyses how this movie represents commoner–aristocracy relationship as an unstable, continuously negotiated construction, albeit wrapped in comedic form. The findings indicate that dangdut is framed as a symbol of spontaneity and egalitarianism, while the keraton is portrayed as a fragile center of authority undergoing image modernization. The cross-class romance narrative functions to normalize Javanese noble–commoner relations while simultaneously concealing the keraton’s internal structural tensions in a manner reminiscent of cultural propaganda. The analysis demonstrates that this film deploys strategies of depoliticization and cultural soft-power to positioning keraton as a progressive institution, thereby destabilizing established symbolic hierarchies. This study contributes new perspectives to understanding cultural representation politics in contemporary Javanese society within Indonesian cinema.